The rationale of the born-digital dossier génétique: Digital forensics and the writing process: With examples from the Thomas Kling Archive. - Ries, Thorsten (Digital Scholarship in the Humanities, 2018)
The article outlines the rationale of the born-digital dossier génétique from a digital forensic perspective in the light of the recent discussion about digital materiality. In its first part, the study addresses theoretical, conceptual, and methodological questions that arise from the specific materiality of the born-digital avant-texte, namely, the dualism of 'forensic materiality' and 'formal materiality' (M. Kirschenbaum) and the role of distributed materiality (J.-F. Blanchette). The article argues that the born-digital record, consisting of digital objects, temporary files, metadata, and fragmented traces of the writing process scattered across multiple system locations, has to be analyzed with regard to the specific historical computing context, its distributed materiality ensemble of hardware, operating system, and application (multi-evidential perspective, J. L. John). Current challenges for born-digital preservation and philological analysis will be discussed. In the second part, the exemplary analysis of several digital drafts and text fragments found on the hard drives of German poet Thomas Kling (1957-2005) sheds light on digital materiality from a practical digital forensic and critique génétique perspective. The following methods will be demonstrated: analysis of fast save artifacts in Microsoft Word documents; draft text recovery from CHK files; file carving and verification of recovery results (true, false positives); recovery of text fragments from drive slack. Digital forensic methodology is in the focus of this article as a tool in the context of archival studies, philology, genetic criticism, and scholarly editing of born-digital material. As born-digital primary records of cultural, social, and political history (private storage media, cloud storage, world wide web content as well as public and semi-public social media posts) come to the archives in increasing numbers and volumes, the forensic perspective on born-digital material, questions of authentic preservation and analysis, bibliographic citability and stability, materiality and their status as a document and evidence as well as legal and ethical issues of preservation, curation and access in the archives become crucial for all humanities disciplines.